EFFECT OF SURGICAL VERSUS NON-SURGICAL TREATMENT OF OBESITY ON BLOOD PRESSURE AMONG NON-COMPLIANT PATIENTS - Mesfer Hussain S Alyami (1) *, Tariq Nasser Bin Yahya Haqawi (2), Layla Hussein Mohammed Awaji (3), Basmaa Yahya Mohammed Alghabri (4), Mohammed Jaber Al Faifi (5), Samira Jaber Al Faifi (3), Mona Ibrahim Hussain Algahtani (6), Ahssan Yahia Abdullah Al sa (Chelonian Research Foundation, 2023)
Introduction: Evaluating the comparative effectiveness of surgical versus non-surgical interventions on blood pressure outcomes is crucial for guiding clinical decisions. Existing literature suggests that bariatric surgeries not only result in significant weight loss but also lead to a notable reduction in blood pressure. This review aims to quantify the effects of each intervention and to identify potential mechanisms underlying these observed effects. Methods: A thorough literature search encompassing multiple electronic databases, including PubMed/MEDLINE, Embase, Cochrane Library, and Scopus, was executed from inception to September 2023. The study selection process involved a two- step approach, initially screening titles and abstracts independently, with subsequent retrieval and assessment of full-text articles against predetermined eligibility criteria. Criteria included adult participants diagnosed with obesity, exclusive consideration of randomized controlled trials (RCTs) and controlled clinical trials (CCTs), and exclusion of pediatric studies, observational designs, reviews, and non-English language publications. Rigorous data extraction procedures, independently conducted by two reviewers, aimed at ensuring the reliability of this systematic review. Results: Eight clinical trials, with a combined sample size ranging from 322 to 2,564 participants, were included in the systematic review, reflecting the diverse nature of obesity and its associated comorbidities. Notable findings from individual trials include a significant reduction in systolic blood pressure by an average of 12 mmHg and diastolic blood pressure by 8 mmHg in the gastric bypass group compared to lifestyle intervention over 12 months. Similarly, sleeve gastrectomy demonstrated a substantial decrease in systolic blood pressure by 15 mmHg and diastolic blood pressure by 10 mmHg compared to pharmacotherapy over 24 months. Collectively, the trials consistently indicate a more significant reduction in blood pressure with surgical interventions, emphasizing their potential cardiovascular benefits in obesity management and highlighting the importance of further research on long-term outcomes. Conclusions: The systematic review of eight clinical trials presents compelling evidence supporting the superior impact of surgical interventions on blood pressure outcomes in individuals with obesity compared to non-surgical approaches. The consistently significant reductions in both systolic and diastolic blood pressure across diverse patient populations underscore the clinical relevance of bariatric surgery in addressing obesity-related hypertension, emphasizing the statistical advantage and potential long-term benefits of surgical interventions in the comprehensive management of obesity-related cardiovascular risks. Keywords: Obesity, Bariatric Surgery, Blood Pressure, Cardiovascular Health, Clinical Trials.